Current trends in glaucoma surgery - Szaflik, Jerzy; Zaleska-Żmijewska, Anna; Izdebska, Justyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of this paper is presentation of new methods of laser and surgery treatment for glaucomatous patients, mainly no perforating operations: deep sclerectomy and viscocanalostomy and new modifications of known very well trabeculectomy.